PENINGKATAN HASIL BELAJAR MELALUI PENGIMPLEMENTASIAN APLIKASI PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN ISPRING - Yuliati Rahmi Firdiana; Bekti Wirawati; Nunuk Suliyastuti (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research is a Classroom Action Research aimed at determining whether the implementation of an Android-based learning application developed using iSpring can improve the learning mastery of fifth-grade students at SDN Pakis 1 Surabaya in the subject of Natural and Social Sciences (IPAS), specifically on the topic of the Human Digestive System. The main objective of this study is to enhance students’ learning mastery. The research was conducted over two cycles, with each cycle consisting of two meetings. Based on the findings, the use of the Android-based learning application created with iSpring proved effective in improving students’ mastery of the Human Digestive System topic. The data showed an increase in the percentage of learning mastery from 29.63% in the pre-cycle to 59.26% in the first cycle and further to 85.18% in the second cycle, with the number of students achieving mastery rising from 8 in the pre-cycle to 16 in the first cycle and 23 in the second cycle.